If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 1x + 2 = 9x + (-6) Reorder the terms: 2 + 1x = 9x + (-6) 2 + 1x = 9x + -6 Reorder the terms: 2 + 1x = -6 + 9x Solving 2 + 1x = -6 + 9x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-9x' to each side of the equation. 2 + 1x + -9x = -6 + 9x + -9x Combine like terms: 1x + -9x = -8x 2 + -8x = -6 + 9x + -9x Combine like terms: 9x + -9x = 0 2 + -8x = -6 + 0 2 + -8x = -6 Add '-2' to each side of the equation. 2 + -2 + -8x = -6 + -2 Combine like terms: 2 + -2 = 0 0 + -8x = -6 + -2 -8x = -6 + -2 Combine like terms: -6 + -2 = -8 -8x = -8 Divide each side by '-8'. x = 1 Simplifying x = 1
| 7x/3-3x/2=70 | | 11x^2-930x-11200=o | | 13g=273 | | 5x+7y=210 | | 7w-6-2w+w-12w+4= | | log(x)=16.5 | | f^2-6f+4=0 | | (-2x^4)+(8x^2)=0 | | -8x-24+6x-15=-5 | | x^2-2x-23.1=0 | | -5/9x=1/3 | | 3x+7+2x-19+x=180 | | 6=5-2x | | P=ad/m | | 3s^2+30s+54=0 | | -5/9x=13 | | 8x-24+6x-15=-5 | | 8x-24+6x--5=-5 | | 57=9-4x | | 3s^2+18s+24=0 | | B=am | | -0.5x^2-1.75x-4.5=0 | | -5(w-6)+7w+2= | | -7y=-14/15 | | Log[6](5x-334)+4=7 | | y=.30x+5 | | -15+3-5= | | 0+3-5= | | -2+3-5= | | -2/5x=-7/15 | | (-15+3)-5= | | 2p+3r=18 |